UAV Magnetic Measurement System for Regional Geomagnetic Survey. Issue 3 (February 2019) - Dai, Jialong; Huang, Kui; Xu, Chaoqun; Zhang, Shaohua; Yi, Zhong; Meng, Lifei; Xiao, Qi; Liu, Chaobo; Wang, bin; Zhang, Chao
Abstract: Commercial UAV airborne magnetic measurement is suitable for regional geomagnetic measurement in terms of its quickness, convenience, efficiency and easy maintenance. The airborne payload performance, weight and volume are often considered for cost and load design during aviation flight. Due to the small size and limited space of commercial drones, it has a very large impact on magnetic survey. Under the constraints of limited space, the performance of the magnetic field detection payload itself and the magnetic properties of the platform become the main factors that restrict the accuracy of magnetic field detection. This paper introduces the high-precision fluxgate magnetic field detector as the three-direction vector payload of magnetic field detection, and expounds its working principle and its high-precision magnetic field detection method. Based on the analysis of payload working environment and detection modes, the on-board magnetic measurement system of the regional geomagnetic survey is designed.